Exhumed hydrocarbon traps on the North Atlantic margin: Stratigraphy, palaeontology, provenance and bitumen distribution, an integrated approach. (23rd December 2019) - Andrews, Steven D.; Decou, Audrey; Braham, Bill; Kelly, Simon R. A.; Robinson, Paula; Morton, Andrew C.; Marshall, John E. A.; Hyden, Fiona
Abstract: Previous work has demonstrated the presence of a number of exhumed hydrocarbon traps in central East Greenland. Re‐evaluation of the stratigraphy alongside detailed investigation of the occurrence of bitumen within the Mols Bjerge and Laplace Bjerg exhumed hydrocarbon traps provides new perspectives on these structures, as well as the petroleum geology of East Greenland and the wider North Atlantic. Sedimentological and stratigraphic studies, augmented with palynological and provenance investigations, have constrained the dating and correlation of the strata exposed in the Mols Bjerge and Laplace Bjerg. Petrographic analysis, alongside analysis of the bitumen identified, has highlighted a much wider distribution of hydrocarbon than previously recognized. It was previously considered that Jurassic strata formed the main reservoir interval within the Mols Bjerge and Laplace Bjerg exhumed hydrocarbon traps. It is shown here that the reservoir intervals in the Laplace Bjerg trap lie within the Late Triassic Ørsted Dal and Vega Sund members, which contain up to 18% pyrobitumen and were previously misidentified as Jurassic. The Jurassic Bristol Elv Formation is the most extensively bitumen stained unit in the Mols Bjerge trap. However, occurrences of pyrobitumen (up to 3%) are recorded throughout the Triassic stratigraphy, including the Early Triassic Wordie Creek Formation. Faults, thick calcrete development and regionally continuous mudstone units play an important role in compartmentalizing the palaeohydrocarbon accumulations. Abstract : The Laplace Bjerg exhumed hydrocarbon trap in East Greenland. Superb exposures of both this fault bounded horst and the tilted fault block of the Mols Bjerge have allowed detailed mapping to be carried out. Both of these exhumed hydrocarbon traps were sealed, at depth, by Cretaceus mudstones, which blanketed much of East Greenland. The identification of pyrobitumen, resulting in a dark staining in the sandstones, has allowed the distribution of the palaeohydocarbon accumulation to be assessed and intra reservoir compartmentalisation by thick, mature calcretes to be recognised. Palynological analysis has determined a Triassic age for the main reservoir units providing evidence for a further potential play in the North Atlantic petroleum system.